Value creation process in majelis taklim for strengthening religious moderation - Ade Tutty Rokhayati Rosa; Irfan Intan Nurdiana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Majelis taklim, as a nonformal Islamic educational institution, plays a strategic role in fostering religious moderation through community-based religious, social, and cultural activities. This study analyzes the value creation process at Majelis Taklim Al-Hikmah in Banceuy Traditional Village and Majelis Taklim Assaadah in Ciater Village, Subang Regency. A qualitative case study was applied using interviews, participatory observation, and documentation, with analysis based on Fuller’s framework: modelling, prioritization, opportunity evaluation, implementation, and measurement and revision. Findings show that both majelis taklim implemented all stages adaptively. Organizational modelling emphasized structured activities, leadership, and resource flow. Prioritization was directed toward congregational needs and nonformal education. Opportunity evaluation responded to social dynamics. Implementation of programs was systematic and aligned with moderation values. Continuous measurement and revision ensured coherence between outputs, outcomes, and the vision of value creation. The study concludes that value creation sustains institutional continuity while strengthening inclusive, harmonious, and culturally contextual religious moderation. It is expected that these findings serve as a reference for developing innovative and sustainable nonformal education strategies to reinforce religious moderation in society